Functional outcomes from a randomized trial of early closure of temporary ileostomy after rectal excision for cancer. Issue 5 (1st February 2019) - Keane, C.; Park, J.; Öberg, S.; Wedin, A.; Bock, D.; O'Grady, G.; Bissett, I.; Rosenberg, J.; Angenete, E.
Abstract : Background: Low anterior resection syndrome (LARS) has a significant impact on postoperative quality of life. Although early closure of an ileostomy is safe in selected patients, functional outcomes have not been investigated. The aim was to compare bowel function and the prevalence of LARS in patients who underwent early or late closure of an ileostomy after rectal resection for cancer. Methods: Early closure (8–13 days) was compared with late closure (after 12 weeks) of the ileostomy following rectal cancer surgery in a multicentre RCT. Exclusion criteria were: signs of anastomotic leakage, diabetes mellitus, steroid treatment and postoperative complications. Bowel function was evaluated using the LARS score and the Memorial Sloan Kettering Cancer Center Bowel Function Instrument (BFI). Results: Following index surgery, 112 participants were randomized (55 early closure, 57 late closure). Bowel function was evaluated at a median of 49 months after stoma closure. Eighty‐two of 93 eligible participants responded (12 had died and 7 had a permanent stoma). Rates of bowel dysfunction were higher in the late closure group, but this did not reach statistical significance (major LARS in 29 of 40 participants in late group and 25 of 42 in early group, P = 0·250; median BFI score 63 versus 71 respectively, P = 0·207). Participants in the late closure group had worse scores on the urgency/soiling subscale of the BFI (14 versus 17; P = 0·017). One participant in the early group and six in the late group had a permanent stoma ( P = 0·054). Conclusion: Patients undergoing early stoma closure had fewer problems with soiling and fewer had a permanent stoma, although reduced LARS was not demonstrated in this cohort. Dedicated prospective studies are required to evaluate definitively the association between temporary ileostomy, LARS and timing of closure. Abstract : Although early closure of the ileostomy is safe in selected patients, functional outcomes have not been investigated. The aim was to compare bowel function in patients who underwent early (8–13 days) or late (more than 12 weeks) closure of an ileostomy after rectal resection for cancer in a multicentre RCT. Patients undergoing early stoma closure had fewer problems with soiling and fewer permanent stomas, but the higher rates of bowel dysfunction in the late closure group did not reach statistical significance. No difference between early and late